The politics of East Asian financial agreement : the case of the CMIM - Pitakdumrongkit, Kaewkamol Karen (S. Rajaratnam School of International Studies, Nanyang Technological University, 2021)
After the Asian Financial Crisis of 1997–8 (AFC), East Asia witnessed an unprecedented degree of regional financial cooperation. The East Asian states’ realisation of their economic vulnerabilities and aversion towards assistance from the International Monetary Fund (IMF) invigorated the policymakers to deepen financial regionalism.40 Several ideas were proposed, including the stillborn Asian Monetary Fund (AMF). While the AMF proposal was rebuffed by the United States and IMF, the idea of a regional funding mechanism continued to be examined.41 In 2000, the ASEAN+3 financial cooperation process was set up, which has formulated several regional financial governance architectures in the areas of reserves-sharing, which were later formalised as the Chiang Mai Initiative Multilateralisation (CMIM), capital market development (Asian Bond Markets Initiative or ABMI for short), and surveillance mechanisms (Economic Review and Policy Dialogue or ERPD, for short, and the ASEAN+3 Macroeconomic Research Office or AMRO, for short).